Personal Trajectories in Russia's Great War and Revolutions, 1914-22 - Lindenmeyr, Adele; Heywood, Anthony; Schenk, Frithjof Benjamin, 1970-; Amacher, Korine, 1963- (Book collections on Project MUSE., 2021)
"This volume investigates how the revolutionary events of 1914-22 shaped biographies both in Russia and Western Europe and how people tried to make sense of the political developments during these years. The case studies allow us to critically evaluate established master narratives about the Russian Revolution and the Civil War. They also enable us to point out the contrast between historical caesuras and the continuity of personal lives, to explore geographical mobility and developments beyond the political centers, to give a voice to historically marginal actors and to juxtapose our concept of "history" with the many-voiced chorus of individual experiences"--